Peran Guru Dalam Prestasi Belajar Matematika Siswa Kelas IV MIN 1 Kota Sidikalang Kabupaten Dairi - Dhita Rahmah Mogia Lingga; Rustam Rustam; Lailatun Nur Kamalia Siregar (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to find out: (1) What is the mathematics learning achievement of class IV MIN 1 Dairi students, (2) What is the teacher's role in the mathematics learning achievement of class IV MIN 1 Dairi students, (3) Why teachers have an important role in students' mathematics learning achievement class IV MIN 1 Dairi. This research uses qualitative research methods in the form of written or oral data from related people. The subjects of this research were the homeroom teachers of class IV C and students of class IV C. In the data collection process this research used three natural methods, namely: observation, interviews and documentation. The data analysis technique is carried out by: data collection, data reduction, data presentation and drawing conclusions. The research results reveal that (1) Learning achievement is the level of humanity possessed by students in accepting, rejecting and assessing information obtained in the teaching and learning process. Learning achievement is a real skill that can be measured by knowledge, attitudes and skills as an active interaction between learning and learning objects during the teaching and learning process to achieve learning outcomes or goals. (2) Teachers must position themselves actively and position themselves as professionals, in accordance with the demands of a developing society and the demands of science and technology that are global. Teachers have the responsibility to bring students to achieve their desired goals. (3) Teachers need to understand the principles of learning because each individual has different conditions. Good student conditions will facilitate the learning process in class. So teachers must arouse readiness, motivate, provide goals, perceptions, understand individual differences, carry out transfers, arouse cognitive and affective skills, arouse students' psychomotor skills, and carry out evaluations to facilitate learning and provide benefits to what has been learned in learning.